Relationship between purse seine dimensions and catch volume in Sikka Regency, Indonesia. Issue 1 (May 2021) - Najamuddin; Musbir; Pale, Christofel Oktavianus Nobel
Abstract: The purse seine is a very productive fishing gear for small pelagic fishes. For purse seines that are actively operated during the day-time, the dimensions of the purse seine are expected to be closely related to the number of fish caught. Field conditions indicate that fishermen use purse seines of varying dimensions. In this context, research is needed. This study aimed to analyze the relationship between purse seine dimensions and the volume of fish caught. This research was conducted in the waters of Sikka Regency, East Nusa Tenggara Province, Indonesia from November to December 2019. The parameters observed included purse seine dimensions, vessel speed and the volume of fish captured per trip. The results showed that purse seine dimensions had a very weak positive correlation (r = 0.088) with catch volume. This shows that the relationship between purse seine dimensions and the volume of fish caught is very weak. Most likely the differences in catch volume were caused by other factors. This is in contrast with other studies showing a significant relationship between the dimensions of the purse seine and the volume of fish caught. In the research location the fishing ground was heavily used, so that the fishing vessels were operating relatively close to one another. This may have created conditions where the net dimensions played a lesser role in increasing the volume of fish caught. In order to avoid one purse seiner being affected by the activities of another purse seiner, it would be necessary to expand the fishing ground or reduce the number of purse seiners operating in that particular fishing ground.